2012
DOI: 10.3941/jrcr.v6i11.1109
|View full text |Cite
|
Sign up to set email alerts
|

Flare Response versus Disease Progression in Patients with Non-small Cell Lung Cancer.Flare Response versus Disease Progression in Patients with Non-small Cell Lung Cancer

Abstract: We present a case report of a patient with metastatic non-small cell lung cancer (NSCLC) who had a series of fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) scans for assessment of response to treatment. A restaging 18F-FDG PET/CT scan after six cycles showed increased FDG activity in the bone lesions with reduced activity in the lung and liver lesions. The increased bone activity was considered to be due to flare phenomenon rather than metastasis. A short inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The development of bone metastases is common in nonsmall cell lung cancer (NSCLC) as about 20-40 percent of patients will be diagnosed with metastatic bone lesions at some point during the course of their disease [1]. In the majority of cases these lesions are osteolytic, but osteoblastic bone metastases in NSCLC have been reported, primarily in adenocarcinoma [2,3]. The finding of new metastatic (bone) lesions will generally prompt a change of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The development of bone metastases is common in nonsmall cell lung cancer (NSCLC) as about 20-40 percent of patients will be diagnosed with metastatic bone lesions at some point during the course of their disease [1]. In the majority of cases these lesions are osteolytic, but osteoblastic bone metastases in NSCLC have been reported, primarily in adenocarcinoma [2,3]. The finding of new metastatic (bone) lesions will generally prompt a change of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Increased FDG uptake was thought to represent osteoblastic activity after an effective therapy [35,36]. This phenomenon had been relatively rare, but recently many cases have been reported, showing that bone flare phenomena are observed on FDG-PET/CT not only for patients with breast cancer, but also for those with non-small cell lung cancer (NSCLC), following the use of anti-VEGF antibodies such as bevacizumab and erlotinib [37][38][39]. The findings of these studies suggest that the addition of immune flare response to monoclonal antibodies on osteoblastic changes may lead to a higher incidence of false positive FDG uptake.…”
Section: False Positive Images Resulting From Monoclonal Antibody Therapymentioning
confidence: 99%
“…In 1999 European Organization for Research and Treatment of Cancer (EORTC) published guidelines for measurement of clinical and subclinical tumor response using FDG-PET [34]. In 2009 a new set of guidelines Positron Emission Tomography Response Criteria in Solid Tumors (PERCIST) [29,35] was proposed and even though the acceptance of these criteria have been quite slow, recent publications support the use of PERCIST over the more simple EORTC criteria [36,37,38,39,40,41,42,43,44,45,46,47,48,49]. This study applied, for the first time in a PET/MR setting, PERCIST measurement.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that SUV values obtained from tumor areas typically decrease following effectively intervention in solid tumors. However, studies have described a temporary increase in SUV, a flare, shortly after chemotherapy administration due to cell swelling, fibroblasts and macrophage infiltration despite therapeutic effect [13,42,43]. Thus, it is currently a widely hold opinion that differentiating between increased FDG uptake due to flare and true disease progression may not be possible early after chemotherapy.…”
Section: Discussionmentioning
confidence: 99%